Effect of 4-week physical exercises on tryptophan, kynurenine and kynurenic acid content in human sweat - Tomasz Saran (Nature Portfolio, 2021)
Abstract The aim of the study was the detection of TRP, kynurenine (KYN), and kynurenic acid (KYNA) in human sweat, and determining whether physical activity affects their content in this secrete. Two different methods were used simultaneously—collection of sweat by means of an absorption pad from the inter scapular region, and collection of a drop of sweat from the region of the forehead. Quantitative determinations of TRP, KYN and KYNA were performed using high performance liquid chromatography with ultraviolet and fluorescence detection. Determinations of sodium was carried out by the method of inductively coupled plasma collision/reaction cell ionization mass spectrophotometry. It was found that physical exercises evoked a decrease in the amount of KYN, and an increase in the amount of KYNA in sweat recorded on day 14, but not on day 28 of training. It appears that physical exercises result in a long-term increase in the kynurenine transaminase activity responsible for the formation of KYNA from KYN. Based on this results, it can be suggested that measurement of TRP, KYN and KYNA in sweat may have diagnostic potential and may help to establish an exercise regime appropriate for the age, gender and health status of rehabilitation patients.